The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00464-008-0100-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidural analgesia diminished pain but did not otherwise improve enhanced recovery after laparoscopic sigmoidectomy: a prospective randomized study

Abstract: Epidural analgesia significantly alleviates pain, reducing the need for opioids during the first 48 h after laparoscopic sigmoidectomy. However, epidural analgesia does not alter postoperative oral intake, mobilization, or length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 20 publications
(25 reference statements)
3
55
2
1
Order By: Relevance
“…The use of laparoscopy significantly reduced LOS [18] and is therefore an implemented part of ERAS. In contrast, the use of epidural analgesia, one of the items in the Consensus Guidelines [3], has no effect on LOS and mobilization [26,27] and hence should be critically investigated as to its impact on LOS and ERAS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of laparoscopy significantly reduced LOS [18] and is therefore an implemented part of ERAS. In contrast, the use of epidural analgesia, one of the items in the Consensus Guidelines [3], has no effect on LOS and mobilization [26,27] and hence should be critically investigated as to its impact on LOS and ERAS.…”
Section: Resultsmentioning
confidence: 99%
“…But its role in laparoscopic surgery is diminished by the fact that it was not correlated [36]. Additional studies demonstrated no reduction in LOS and earlier oral food intake by using epidural anesthetics [27]. …”
Section: Resultsmentioning
confidence: 99%
“…During the operation, a solution of 4 ml morphine 0.03% and 116 ml rupivocaine 2% was placed in a Baxter pump at a steady flow of 5 ml/h, which was administered perioperatively and up to 48 h postoperatively [12].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a 2008 study by Zingg et al [18] found equivalent lengths of stay for 79 EA and CA patients who had undergone laparoscopic colectomy during a prospectively randomized trial. Turunen et al [23] also reported no change in length of stay for EA recipients; their study concerned prospectively gathered data of 60 elective colectomies for patients with complicated diverticular disease, treated in an ERP. Our data were derived from a larger patient population, spanning multiple institutions and recovery protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Ileus is thought to be caused by a combination of several factors, including pain, sympathetic response to surgical insult, and opioid use [25]. Since EA is associated with decreased postoperative narcotic use, it may be inferred that it should reduce ileus rates as well [1,18,23]. Furthermore, it has been theorized that EA attenuates the stress response that is in part responsible for gut dysfunction after surgery [26].…”
Section: Discussionmentioning
confidence: 99%